Primary Umbilical Endometriosis: Unusual and Rare Clinical Presentation - Fuminori Taniguchi; Eriko Hirakawa; Yukihiro Azuma; Chihiro Uejima; Keigo Ashida; Tasuku Harada (Case Reports in Obstetrics and Gynecology)
Primary umbilical endometriosis is a rare disorder and is defined as the presence of ectopic endometrial tissue within the umbilicus. A patient with painful mass in the umbilicus during menstrual period is studied in this paper. The possibility of subcutaneous endometriosis should be considered when an umbilical mass is detected despite the absence of previous surgery. In this case, urachal cancer, urachal remnant, umbilical endometriosis, and its malignant transformation were among the diseases considered in the differential diagnosis. Complete excision and histology are necessary to obtain a definitive diagnosis and optimal treatment for umbilical subcutaneous endometriosis.